ANALISIS PERSEPSI KONSUMEN TERHADAP KEBIJAKAN ATMOSFIR TOKO SERTA PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PADA RITEL XING MART DI PONTIANAK - Hiong, Lauw Sun (MABIS, 2013)
Retail marketing is a way in which a smaller amount of sales compared to the no retail, however the retail market is not limited in number and also be flexible. There is a change in marketing activities, so that the company tends to sell large quantities of sales are now starting to serve with smaller quantities. Characteristics of the retail industry that does not require special skills and higher education to learn, so many Indonesian people especially those belonging to the category of small and medium enterprises is included in the retail industry. In relation with the situation, the marketing strategy should be a top priority of every company in order to achieve its goals. The main purpose of the marketing concept is to provide satisfaction to consumers in meeting their wants and needs. One of the marketing strategies in store or retail outlet is designing the atmosphere of the store. This study is a descriptive study using a quantitative survey methods and techniques of data collection using questionnaires. Test results of the multiple regression, showed variable exterior, interior, and salesperson influence on consumer purchase decisions. Based on partial test showed a result that store atmospheric variables such as, exterior, interior, and the clerk has a significant influence on the purchase decision variables.